(3YdGbI GdhYi GdGNJHGQi HGdCOGA GdfGJL ef GNJHGQ JMUjdi dGNJjGQ ef eJYOO eHfi hab fehPL QGT Ydi WdHI GdeQMdI GdKGfhjI HOhdI GdchjJ (B/ s - (3SGei TWjW YGjO GdYfRis; (3CeGfi SYjOI SjO EHQGgje (B: s; (3QLGA eMehO CHhYdGe (B: s ((3GdbGgQI (B: s (3SGei TWjW YGjO GdYfRi (B: s, 2015)
(3JgOa GdOQGSI GdMGdjI Edi GdJYQa Ydi YdGbI GdhYi GdGNJHGQi HGdCOGA GdfGJL ef GNJHGQ JMUjdj dGNJjGQ ef eJYOO eHfi hab fehPL QGT Ydi WdHI GdeQMdI GdKGfhjI HOhdI GdchjJ(B: (3h dJMbjb Pdc Je GNJjGQ YjfI JchfJ ef (B(284) (3WGdHkG h WGdHI ef WdHI GdUa GdKGfi YTQ KGfhi ai Ohdg GdchjJ h Je EYOGO ebjGSjf ef bHd GdHGMK(B: (3Jchf GdChd ef (B(59) (3HfOG jbjS ESJQGJjLjGJ h Yi GNJHGQi (B((3GdMceI GdGNJHGQjI(B) (3h jJchf ef KdGKI eMGhQ gi(B: (3EOGQI GdhbJ(B: (3JLfH GdJNejf(B: (3GdJNejf(B: (3NUGFU HfGA GdHfhO GdGNJjGQjI(B: (3HjfeG Jchf GdebjGS GdKGfi GdeHfi hab fehPL QGT ai UhQJg GdfgGFjI (B(58) (3HfOkG dbjGS GdCOGA GdJMUjdi ai GdeSJhjGJ GdeYQajI GdCQHYI GdChdi dJUfja Hdhe hgi(B: (3GdJPcQ(B: (3Gdage h GdGSJjYGH(B: (3GdJWHjb(B: (3h GdJMdjd s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ h GdHMhK GdJQHhjI (B- (3bSe Yde GdfaS GdJQHhis
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdENJHGQ GdJMUjdis; (3GdhYi GdGNJHGQis; (3fehPL QGTs